2011
DOI: 10.4250/jcu.2011.19.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Syndrome with a Delayed Onset of Heart Failure

Abstract: A 59-year-old man treated with pneumococcal meningitis 4 months ago was hospitalized for acute heart failure and performed aortic valve replacement by rupture of aortic valve. The frequent association of pneumococcal meningitis and endocarditis is known as Austrian syndrome. Though Austrian syndrome is a clinically rare disease, the evolution of pneumococcal endocarditis is very aggressive and associated with high mortality, and early recognition for evidence of endocardial lesion in patients with pneumococcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Streptococcus pneumoniae remains as the predominant organism for community acquired pneumonia and meningitis, but its role in causation of infective endocarditis has fallen to less than 3% cases from 15–30% in the pre-penicillin era [ 4 , 5 ]. It is not uncommon that, during an episode of invasive pneumococcal infection like meningitis; the possibility of valvular involvement is easily overlooked in absence of peripheral stigmata of infective endocarditis [ 6 , 7 ] resulting in late diagnosis of endocarditis [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae remains as the predominant organism for community acquired pneumonia and meningitis, but its role in causation of infective endocarditis has fallen to less than 3% cases from 15–30% in the pre-penicillin era [ 4 , 5 ]. It is not uncommon that, during an episode of invasive pneumococcal infection like meningitis; the possibility of valvular involvement is easily overlooked in absence of peripheral stigmata of infective endocarditis [ 6 , 7 ] resulting in late diagnosis of endocarditis [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association of PE with pneumococcal meningitis (and at times, pneumococcal pneumonia) is often referred to as Austrian syndrome. Few cases of Austrian syndrome are reported in the medical literature [ 16 , 17 ]. Martínez et al reported a concerning increase in the resistance of pneumococci to penicillin, but the study did not show any effect of penicillin-resistant strains on clinical characteristics, complications, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Unique to pneumococci is a condition called Austrian Syndrome, which consists of meningitis, pneumonia, and endocarditis and is most often observed in middle-aged men with pre-existing conditions such as alcoholism. Although Austrian Syndrome is clinically rare, it is highly aggressive and often fatal because endocarditis is recognized too late [8].…”
Section: Introductionmentioning
confidence: 99%